2012
DOI: 10.1136/annrheumdis-2012-201821
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the 2011 ACR/EULAR preliminary remission criteria compared with DAS28 remission in unselected patients with rheumatoid arthritis

Abstract: Patients fulfilling the new remission criteria tend to be not only free from active RA, but also from other disabling diseases. If these criteria are applied in clinical practice to guide treatment decisions, the impact of comorbidity should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 19 publications
7
35
0
1
Order By: Relevance
“…El motivo es que la definición de remisión según el DAS28, ampliamente utilizada en nuestra práctica clínica, tiene importantes limitaciones como, por ejemplo, que pacientes con varias articulaciones inflamadas y progresión radiológica puedan considerarse en remisión según este índice 25 . Los criterios de remisión ACR/EULAR, inicialmente diseñados para uso en ensayos clínicos 24 y validados en condiciones de práctica clínica diaria 26 , son más estrictos y solo un 7-20% de pacientes en estudios observacionales los cumplen [27][28][29] . Además, también hay que tener en cuenta que factores ajenos a la AR, como caracterís-ticas subjetivas del paciente 30 o la presencia de comorbilidades 29 , pueden incidir en que algunos pacientes no cumplan criterios de remisión.…”
Section: Resultados Y Discusiónunclassified
“…El motivo es que la definición de remisión según el DAS28, ampliamente utilizada en nuestra práctica clínica, tiene importantes limitaciones como, por ejemplo, que pacientes con varias articulaciones inflamadas y progresión radiológica puedan considerarse en remisión según este índice 25 . Los criterios de remisión ACR/EULAR, inicialmente diseñados para uso en ensayos clínicos 24 y validados en condiciones de práctica clínica diaria 26 , son más estrictos y solo un 7-20% de pacientes en estudios observacionales los cumplen [27][28][29] . Además, también hay que tener en cuenta que factores ajenos a la AR, como caracterís-ticas subjetivas del paciente 30 o la presencia de comorbilidades 29 , pueden incidir en que algunos pacientes no cumplan criterios de remisión.…”
Section: Resultados Y Discusiónunclassified
“…Reported prevalence rates of remission according to the new criteria range between 5% and 25% 2,3,4,5,6,7,8,9 , a marked decline compared to reported DAS-based remission rates between 25% and 50%, and even one instance of 90% 10 . We now refer to Disease Activity Score (DAS)-based remission as minimal disease activity.…”
mentioning
confidence: 81%
“…The set of 4 proposed criteria -2 clinical trial criteria and 2 clinical practice criteria -have since been the subject of several validation studies. Rheumatology researchers have shown that clinical trial criteria requiring a tender joint count, swollen joint count, C-reactive protein (CRP) and patient global assessment ≤ 1 or a Simplified Disease Activity Index (SDAI) ≤ 3.3 perform well in both trial and clinical-practice settings 2,3,4,5,6 .…”
mentioning
confidence: 99%
“…Therefore, the ACR and EULAR convened a joint committee to redefine RA remission; they proposed two new definitions of remission in 2011 (Table 3), both of which can be uniformly applied and are widely used in RA clinical trials (34). Although good performance has been reported for the new remission criteria, indicating that patients fulfilling the criteria tend to be free from active RA (35)(36)(37), several articles have reported that the major reason for not achieving remission based on the new definition is due to the patient global assessment (PGA), which could be influenced by non-inflammatory factors, including low back pain, fatigue, and fibromyalgia (38,39). The validity of the criteria is still being discussed.…”
Section: New Remission Criteriamentioning
confidence: 99%